“The Cat Looks at the Dog Not with Hatred, but Contemptuously”: Čapek’s Remarks on the Animal Mind - Gawarecka, Anna (Porównania, 2022)
he book by Karl Čapek Měl jsem psa a kočku (I had a dog and a cat) appeared (posthumously) in 1939 in the Czech publishing market. This publication, which consisted of several essays, a story about the fox terrier Dašenka and a humorous guide to dog breeds, was mostly treated by literary scholars as some kind of hybrid bricolage of a miscellaneous texts. The animal stories published in this book draw their thematic material from everyday and empirical observation and do not need to use systems of cultural references and imagination. Their reception, however, requires common knowledge, available to those (i.e., in fact, to everyone) who have ever dealt with domestic animals and thus are able to confirm these observations, confront them with their own experience and, as a result, appreciate the accuracy and insight of the diagnoses offered by the author. The paradoxical conclusions of Čapek’s remarks throw readers out of their cognitive routine and show that the problem of animal emotional and intellectual life is more complicated than is usually considered. The narrative portraits of dog and feline heroes are primarily used to build anthropological models for which the patterns of animal behaviour constitute a convincing (because reduced to simplified “basic” behavioural matrices) exemplification.